Impact of premenstrual syndrome symptoms on sport routines in nonelite athlete participants of summer Olympic sports - Prado, R. C. R.; Willett, H. N.; Takito, M. Y.; Hackney, A. C. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Most women during their lifetime experience a combination of premenstrual syndrome (PMS) symptoms (eg, menstrual cramps) before and often to the end of menstruation. However, the impact of these symptoms on sport routines (eg, performance, training absence) during phases around menstruation is still unclear. Therefore, we investigated the impact of PMS symptoms on sport routines among nonelite athletes over 3 phases related to menstruation.